Analisis Build Time Continuous Integration pada Multi Node Jenkins Menggunakan Metode Cache - Saputro, Febriyan Adji; Nugroho, Muhammad Agung; Sahputra, Eka; Segara, Alon Jala Tirta (LPPM STIKI MALANG, 2025)
In the era of modern software development, the speed and efficiency of application build processes have become critical factors in enhancing the productivity of development teams. Jenkins, as a popular CI/CD tool, can be utilized to perform distributed builds across multiple servers. However, long build times remain a significant challenge, especially for container-based applications that require numerous dependencies and compilation stages. This study proposes a method to optimize build time by leveraging caching mechanisms. The proposed method utilizes cache storage to save frequently used build artifacts, thereby reducing the time required for recompilation in subsequent builds. In this research, experiments were conducted to compare the build time of container-based applications before and after implementing the caching method. The results of this study indicate that applying caching techniques to container-based applications can improve build speed by approximately 43% to 76%. This finding demonstrates that caching is highly effective in enhancing build time efficiency within Jenkins’ multi-node architecture. Consequently, this optimization not only accelerates the build process but also reduces computational resource consumption, thereby supporting more efficient and cost-effective CI/CD practices.